12-Weeks programmed aerobics dance reduced body mass index and waist circumference of young women (Bangladesh Journal of Medical Science, 2016)
Background: Body composition is one of the parameters to evaluate the level of physical fitness. Body composition can be assessed by simple tools like body mass index and waist circumference. This tools are useful also to predict risks for cardiovascular diseases such as metabolic syndrome and dyslipidemia in which the prevalence continues to increase worldwide. Programmed aerobic dance is one of the physical exercises that is quite popular these days that is expected can reduce body mass index and waist circumference.Objective: To determine the effect of programmed aerobic dance on body mass index and waist circumference.Method: This pre and post-test experimental study was conducted on 33 female individuals aged 15-30 years of Jenderal Soedirman University Purwokerto, Central Java. Programmed aerobic dance as intervention was given for twelve weeks in Siscas Gymnasium. Health status and PAR-Q (Physical Activity Readiness Questionnaire) were assessed before enrolling this study. Body mass index and waist circumference were measured before and after intervention. For statistical analyses, basic descriptive statistics and paired t-test or Wilcoxon analyses were applied for dependent variables.Result: Programmed aerobic dance significantly reduced body mass index from 22, 89 (before intervention) to 22, 34 (after intervention), p < 0,05. Subjects had lower waist circumference after intervention (75 cm compared with 72 cm, p < 0,001).Conclusion: Twelve weeks programmed aerobic dance reduce body mass index and waist circumference.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.376-380